Potensi Tanaman Ganjan (Artemisia vulgaris) dalam Penyembuhan Luka Sayat pada Tikus (Sprague Dawley): The Potential of Ganjan (Artemisia vulgaris) in Wound Healing in Rats (Sprague Dawley) - Istiqomah, Indriana Noor; Mashuri; Abdillah, Achlish; Azizah, Laili Nur (Jurnal Tumbuhan Obat Indonesia, 2024)
Recent studies have focused on exploring natural remedies to accelerate wound healing. One such herbal plant is the Ganjan plant (Artemisia vulgaris), which contains essential oils, coumarins, flavonoids, triterpenoids, and phenolic acids, which make it a good candidate for natural remedies. This study analyzed the wound-healing potential of the Ganjan plant using a true experimental research design on 16 male Sprague Dawley rats. The rats were divided into four groups and subjected to different treatments, including a negative control group without treatment (K1), a 10% Ganjan herbal extract ointment group (K2), a 30% Ganjan herbal extract ointment group (K3), and a positive control group with 10% betadine ointment (K4). The ointments were applied once daily for 21 days or until the wounds healed, and wound area measurements were taken every three days. The results showed that the 10% and 30% Ganjan ointments effectively reduced the wound area, and there was no difference in wound contraction between 10% and 30% Ganjan ointment and 10% Betadine. The study concludes that Ganjan plant extract ointment is an effective natural remedy for wound healing and that the best results are seen in the 30% Ganjan extract ointment group.